2010
DOI: 10.1378/chest.09-0959
|View full text |Cite
|
Sign up to set email alerts
|

Early Anticoagulation Is Associated With Reduced Mortality for Acute Pulmonary Embolism

Abstract: We report an association between early anticoagulation and reduced mortality for patients with acute PE. We advocate further study with regard to comorbidities to assess the usefulness of modifications to hospital protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
163
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(174 citation statements)
references
References 46 publications
(40 reference statements)
3
163
1
7
Order By: Relevance
“…Third, data are lacking to compare the availability and contemporaneous use of risk stratification methods, including serum biomarkers, for patients diagnosed with PE. Fourth, no prior data have documented the frequency of use of empiric anticoagulation in the ED, an intervention that may affect outcome (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, data are lacking to compare the availability and contemporaneous use of risk stratification methods, including serum biomarkers, for patients diagnosed with PE. Fourth, no prior data have documented the frequency of use of empiric anticoagulation in the ED, an intervention that may affect outcome (5).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has suggested that delays in anticoagulation are associated with increased short-term adverse events, including recurrence of VTE (18,19). Two independent reports have found an increase in mortality in ED patients with PE who did not receive heparin until after hospital admission, compared with patients who received heparin in the ED (5,18,19). Moreover, Smith et al (5) found that the time to heparin administration was an independent predictor of mortality in a logistic regression equation that was adjusted for the cumulative effect of comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The therapy of IV UFH requires monitorization on activated partial thromboplastin time, so patients with acute PE need hospitalization. The efficacy of IV UFH also depends upon achieving a therapeutic level of heparin within the first 24 h of treatment [11]; because achieving this sometimes fails, inadequate initial heparin therapy may increase the probability of recurrent PE for at least 3 months despite ongoing therapeutic anticoagulation [12]. …”
Section: Discussionmentioning
confidence: 99%
“…If untreated, it has an overall mortality of up to 26% [12]. Anticoagulation reduces mortality and recurrence of pulmonary embolism [13]. All our patients were asymptomatic, and all of them had undergone a prior staging contrast-enhanced CT that missed the thrombotic disease in half of them because of the inadequacy of the CT protocol, which should have been a CT pulmonary angiography.…”
Section: Discussionmentioning
confidence: 99%